Health-related quality of life following heart surgery (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This study evaluates the differences in preoperative and postoperative health-related quality of life of the patients following heart surgery and observed the factors that influence quality of life changes. This prospective observational study involved two parameters from the SF-36 questionnaire before and one year after heart surgery in a single surgeon’s practice. At the baseline assessment of the study observed 140 patients, predominantly were male in both study groups. The mean age was 56.8 ± 4.2 years, 64.7 ± 7.4 years in Group of patients age ≤ 60 years and age >60 year’s respectively. In elderly aged group, patients have greater risk of co-morbidity, operative complications, and low preoperative as well as postoperative quality of life score. There was an overall improvement in all majority health domains of the SF-36 questionnaire among study population. Statistical results from Logistic multivariate analysis demonstrates a greater value of preoperative mental component summary scores (p=0.08), and physical component summary scores (p=0.01) as potential risk factors for non-improvement following heart surgery. Although, elderly patients (age >60 year’s) with greater operative risk have low preoperative quality of life score, but demonstrate an equal improvement in most of the health domains following heart surgery as like as younger study population.